The last segregated hour: the Memphis kneel-ins and the campaign for Southern church desegregation - Haynes, Stephen R. (Oxford University Press, 2012)
"The start of a new movement across the South": the first kneel-ins, 1960 -- "Christ did not build any racial walls": church desegregation campaigns, 1961-65 -- "This spectacle of a church with guarded doors": the Memphis campaign of 1964 -- "Like a child that had been unfaithful": a church-related college and a college-related church -- "A time when the bare souls of men are revealed": Southern Presbyterians respond -- "You're going to have to go out there yourself": church people -- "Our presence at the church is itself an act of worship": White visitors -- "You will only know my motivation when you open the door": Black visitors -- "Mama, why don't they just let them in?": children -- "The greatest crisis in the 120-year history of our church": defiance, intervention, and schism -- "Not the church's advantages, but the city's disadvantages": wrestling with the past at Second Presbyterian Church -- "A season of prayer and corporate repentance": wrestling with the past at Independent Presbyterian Church